Disinfectant Spraying Robot to Prevent the Transmission of the Covid-19 Virus Based on the Internet of Things (IoT) - Indah Sulistiyowati; Moh Imam Muhyiddin (Journal of Electrical Technology UMY, 2021)
One way to prevent the transmission and spread of Covid-19 is to always keep ourselves and our environment clean. Maintaining personal and environmental hygiene can be done by using antiseptics and disinfectants. Disinfectants that are not used properly will be bad for humans. That is why so far the spraying of disinfectants for the prevention of COVID-19 has been carried out by human workers who are dressed in complete Personal Protective Equipment (PPE) using manual sprayers. This is certainly very risky to humans who do the spraying manually. The objective of this research is to minimize the risk of spraying disinfectants, by using a robotic power to spray disinfectant based on the Internet of Things (IoT) and a camera. This robot is operated by using a smartphone while to determine the environmental conditions around it is used a camera. From the test results, it obtained data that the robot works well and is quite reliable due to the wider scope limit because it uses an IoT connection to communicate with smartphones. The results of camera readings on laptops are also quite clear, although the higher the resolution on the display, the lag time required to transfer images to the laptop affects.